Media Sosial dan Ketahanan Keluarga: Mengurai Tantangan dan Solusi dalam Menghadapi Perselingkuhan Virtual - Kholik, Kusnul; Rohmatiq Azza, Nala (JAS MERAH: Jurnal Hukum dan Ahwal al-Syakhsiyyah, 2024)
The development of technology and social media has had a significant impact on various aspects of life, including family relationships. On the one hand, social media provides easy communication and access to information, but on the other hand, its uncontrolled use can pose a serious threat to household harmony, such as increasing cases of virtual infidelity. This research aims to analyze the influence of social media on family resilience, especially in the context of virtual infidelity, and offers solutions based on religious, psychological and social regulatory approaches. The research results show that virtual infidelity occurs due to ease of access, lack of communication within the family, and dissatisfaction in the husband-wife relationship. The impacts include broken household relationships, emotional disturbances in partners and children, and psychological trauma. To overcome this problem, a religion-based approach emphasizes the importance of self-monitoring and Islamic etiquette in using social media. The psychological approach involves effective communication, education about healthy use of social media, and joint activities to strengthen family bonds. Apart from that, the role of government and society in regulating social media content and providing family counseling services is also an important key.